2022
DOI: 10.3390/met12010112
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Sintering Process for the Production of Magnetocaloric La(Fe,Si)13-Based Composites

Abstract: A one-step sintering process was developed to produce magnetocaloric La(Fe,Si)13/Ce-Co composites. The effects of Ce2Co7 content and sintering time on the relevant phase transformations were determined. Following sintering at 1373 K/30 MPa for 1–6 h, the NaZn13-type (La,Ce)(Fe,Co,Si)13 phase formed, the mass fraction of α-Fe phase reduced and the CeFe7-type (La,Ce)(Fe,Co,Si)7 phase appeared. The mass fraction of the (La,Ce)(Fe,Co,Si)7 phase increased, and the α-Fe phase content decreased with increasing Ce2Co7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Considering Equations ( 16), ( 17) and (19), it was concluded that n Fe 2 J Fe−Fe + n Co 2 J Co−Co + 2n Fe n Co J Fe−Co would increase. Next, considering that the fourth term −2n Fe n R J Fe−R in Equation (15), and as n Co increases, n Fe decreases while n R remains unchanged, −2n Fe n R J Fe−R would increase. In general, it can be obtained that all four terms in Equation ( 15) increase with the increase of n Co .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering Equations ( 16), ( 17) and (19), it was concluded that n Fe 2 J Fe−Fe + n Co 2 J Co−Co + 2n Fe n Co J Fe−Co would increase. Next, considering that the fourth term −2n Fe n R J Fe−R in Equation (15), and as n Co increases, n Fe decreases while n R remains unchanged, −2n Fe n R J Fe−R would increase. In general, it can be obtained that all four terms in Equation ( 15) increase with the increase of n Co .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in order to improve the magnetic entropy change of the compound, other rare earth elements can be used to partially replace the La element in the compound, but this will further reduce the Curie temperature. This is very unfavorable to the practical application of the compound [13][14][15]. To address the mentioned problem, our research group has selected low-silicon compound LaFe 11.4 Si 6 as the research object and prepared La 0.8 Ce 0.2 (Fe 1−x Co x ) 11.4 Si 1.6 (x = 0.02, 0.04, 0.06) by partially replacing La and Fe with rare earth element Ce and transition metal Co [16].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetocaloric and magnetostrictive materials have also attracted significant attention. Zhong et al [7] prepared magnetocaloric La(Fe,Si) 13 /Ce-Co composites via a one-step sintering process. Using 15 wt.% Ce 2 Co 7 as a dopant and binder, the Curie temperature (T C ) increased from 212 K to 331 K, and the change in the maximum magnetic entropy (−∆S M ) max decreased from 8.8 to 6.0 J/kg•K under a 5 T field.…”
Section: Contributionsmentioning
confidence: 99%
“…La(Fe, Si) 13 -based compounds are considered as promising magnetic refrigeration materials for room temperature refrigeration and have received extensive attention and research, while there are still relatively fewer magnetic refrigeration candidates for the liquid hydrogen temperature region. [9][10][11] The Ericsson cycle is considered to be the optimal thermodynamic cycle for hydrogen liquefaction, which consists of two isothermal processes and two isomagnetic processes. Therefore, the development of magnetic refrigeration materials with table-like magnetic entropy changes for hydrogen liquefaction is essential.…”
Section: Introductionmentioning
confidence: 99%